Drug utilization evaluation of anticancer drugs in a charitable hospital - Mathew, Maneesha; Mateti, Uday Venkat; Saj, Neethu; Philip, Malona Lilly; Shetty, Vijith (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Evaluating the prescribing patterns of anticancer and supportive care drugs is necessary for ensuring effectiveness and patient's quality of life. Aim: This study aims to evaluate the prescribing patterns in patients receiving chemotherapy. Settings and Design: A prospective observational study was conducted in the Department of Medical Oncology at Justice K. S. Hegde Charitable Hospital. Methods: The study was conducted for 8 months from September 2017 to April 2018. Cancer patients who were above 18 years and are on chemotherapy along with supportive care medications were enrolled. Statistical Analysis: Data were analyzed using descriptive statistics. Continuous data were expressed as mean ± standard deviation, and the nominal data were expressed as frequency and percentages. Results: Among 230 patients, majority of patients were in the age group of 45–60 years (47%), females (51.7%), Stage III (51.3%), solid tumor (85.5%), breast cancer (21.7%), doublet regimen (60.4%), who received doxorubicin and cyclophosphamide (36%) in breast cancer while paclitaxel and carboplatin (16.52%) were mostly prescribed among the different cancer types. The most commonly prescribed supportive care medications were dexamethasone (100%), ranitidine (100%), filgrastim (67.4%), tramadol and paracetamol (23.91%), and levofloxacin (9.56%). The percentage of drugs prescribed from the National List Essential Medicine and the World Health Organization (WHO) model list was 80.84% and 78.92%, respectively. Conclusion: According to the WHO core prescribing indicators, the average number of drugs per prescription was 9.63. Majority of the cancer patients were prescribed with paclitaxel and carboplatin (16.52%); dexamethasone and ranitidine (100%) were coadministered in all patients during their chemotherapy cycles.
Keywords: Cancer; chemotherapy; prescribing patterns; World Health Organization